IMPLEMENTASI MODEL DELONE DAN MCLEAN TERHADAP KESUKSESAN PENERAPAN DATABASE REPLIKASI PADA DIREKTORAT JENDERAL BEA DAN CUKAI - Sri Lestari; Dies Larassanti Rahayu (CKI ON SPOT, 2019)
Data presentation is one of the main performance indicators for agencies of theDirectorate General of Customs and Excise, especially the Echelon II unit, namely the Directorate of Customs and Excise Information at the Subdirectorate of Data Management and Services. The large number of data requirements required makes the server load on the database even greater, for this purpose a replication database is called a database report as a database that is used as a database for data retrieval. This study aims to analyze the factors that influence satisfaction in the use and utilization of the database report as a source of data in presenting datausing the Delone and McLean models. In measuring the success of the system there are variables in information quality, system quality, service quality, usage, and user satisfaction that are associated with the net benefits received by individuals or organizations. The research method used is by distributing questionnaires through the Google Forms link to employees in the Data Management and Service Subdirectorate, the results of the questionnaire were processed usingSEM-PLS techniques using SmartPLS 3.0 tools. Based on the results of the analysis, the percentage of success in using the database report is 75.7% at level 4 between 61% - 80%, which is success, but there still needs to be a lot of improvement to become a better government agency.